Moving out of sports: A sociocultural examination of Olympic career transitions - Barker, D.; Barker-Ruchti, N.; Rynne, S.; Lee, J. (International Journal of Sports Science and Coaching, 2014)
This article outlines sociocultural learning theory, shows how this theory can be used to examine end-of-career athletic transitions, and stimulates discussion on the implications of this framework for sport professionals. The central question addressed is how learning in elite sport affects participation in activities beyond sporting settings. Data from in-depth, semi-structured interviews with three former Olympians are presented. The interpretation suggests that: 1) movement to new social settings involves abandoning some elements of athletic dispositions and developing new elements, 2) transitions are affected by prior learning in sport and the characteristics of new settings, and 3) learning in sporting environments is often unintentional or implicit. The results encourage practitioners to acknowledge the effort involved in developing new dispositions in different settings. They support a case-specific view of transitions where `success` is considered in contextual terms. Further, the data highlight a need for sport professionals to recognize tacit learning.